2003
DOI: 10.1007/bf02976865
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipids fromBombycis corpus and their neurotrophic effects

Abstract: Three phospholipids (4-6) and three aromatic amines (1-3) were obtained from the methanol extract of Bombycis corpus. Based on spectral data, their structures have been elucidated as nicotiamide (1), cytidine (2), adenine (3), 1-O-(9Z-octadecenoyl)-2-O-(8Z,11Z-octadecadienoyl) sn-glycero-3-phosphorylcholine (4), 1,2-di-O-hexadecanoyl-sn-glycero-3-phosphorylcholine (5) and 1,2-di-O-9Z-octadecenoyl-sn-glycero-3-phosphorylcholine (6). We examined the effects of compounds on synthesis of NGF in cultured astrocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…11,12) In the present study, we found that BLP-conditioned media of C6 and primary astrocyte cells caused the induction of PC 12 neurite outgrowth. Since NGF is known to be an endogenous molecule that contributes to the differentiation of PC12 cells, 13) we hypothesized that BLP might enhance NGF secretion and synthesis in astrocyte cells.…”
Section: Discussionsupporting
confidence: 51%
“…11,12) In the present study, we found that BLP-conditioned media of C6 and primary astrocyte cells caused the induction of PC 12 neurite outgrowth. Since NGF is known to be an endogenous molecule that contributes to the differentiation of PC12 cells, 13) we hypothesized that BLP might enhance NGF secretion and synthesis in astrocyte cells.…”
Section: Discussionsupporting
confidence: 51%
“…Five fatty acids were isolated from B. batryticatus : meso-erythritol ( 3 ), citric acid ( 4 ), decanoic acid ( 5 ), stearic acid ( 6 ) and palmitic acid ( 7 ) [ 43 , 44 , 45 ]. Seven derivatives of fatty acids in B. batryticatus were identified: (4 E ,2 S ,3 R )-2- N -octadecanoyl-4-tetradecasphingenine ( 8 ), (4 E ,6 E ,2 S ,3 R )-2- N -eicosanoyl-4,6-tetradecasphingadienine ( 9 ), (4 E ,2 S ,3 R )-2- N -eicosanoyl-4-tetradecasphingenine ( 10 ), (4 E ,6 E ,2 S ,3 R )-2- N -docosanoyl-4,6-tetradecasphingadienine ( 11 ), 1,2-di- O -hexadecanoyl-sn-glycero-3-phosphorylcholin ( 12 ), 1- O -(9 Z -octadecenoyl)-2- O -(8 Z ,11 Z -octadecadienoyl)-sn-glycero-3-phosphorylcholin ( 13 ) and 1,2-di- O -9 Z -octadecenoyl-sn-glycero-3-phosphorylcholin ( 14 ) [ 46 , 47 ].…”
Section: Chemistrymentioning
confidence: 99%
“…In 1996, four nucleotides were detected in B. batryticatus by Li et al (1996) through HPLC method, including uracil ( 19 ), uridine ( 20 ), hypoxanthine ( 21 ) and xanthine ( 22 ), and among them, uracil content was highest [ 47 ]. Later, in 2003, uracil ( 19 ), cytidine ( 23 ) and adenine ( 24 ) were isolated from B. batryticatus by Kwon et al (2003b) [ 49 ].…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Further, BB contains different proteins, peptides, fatty acids, flavonoids, nucleosides, steroids, coumarin, and polysaccharides [7]. Moreover, BB has recently been shown to exhibit neuroprotective and anti-necrotic effects in pyramidal neurons, neurotrophic (upregulation of nerve growth factor) and anti-oxidative (upregulation of superoxide dismutase, SOD) effects in astrocytes, and antiapoptotic effects (inhibition of lipid peroxidation) in hippocampal neurons [7][8][9]. Recently, Hu et al reported that BB exerts neuroprotective, anti-oxidative, and anti-apoptotic effects against pentylenetetrazole-or H 2 O 2 -induced epileptic neurotoxicity via the PI3K/Akt signaling pathways [10].…”
Section: Introductionmentioning
confidence: 99%